Complaints of Musculoskeletal Disorders on Sales Promotion Girl at Cosmetic Stores in Surabaya, Indonesia - Mawaddah, Salsa Daffania; Widajati, Noeroel (Folia Medica Indonesiana, 2021)
Highlight: • Standing position duration and shoe characteristics to MSDs's complaints on sales promotion girls at cosmetic stores in Surabaya were analyzed. • There was no correlation between height of heels with complaints of MSDs and shoe type, while, the duration of standing position and complaints of MSDs were correlated. Abstract: One of the occupations that have a risk of Musculoskeletal Disorders (MSDs) is sales promotion girl (SPG), especially the SPG at a cosmetic store, because their job position is mostly done by standing and wearing high heels. This study aimed to analyze the correlation between duration of standing position and shoe characteristics to complaints of MSDs on sales promotion girl at cosmetic stores in Surabaya. This study was quantitative research with observational analytic research, where the data collection was carried out by cross-sectional. This research was conducted at 21 cosmetic stores from three shopping centers in Central Surabaya. The population in this study was 64 SPG. The sample was taken using simple random sampling with exclusion criteria, so that 47 people were obtained. The independent variables consisted of duration of standing position and shoe characteristics included shoe type and the height of heels. The dependent variable was complaint of MSDs. The data analysis was carried out using the Spearman correlation test. The result showed that there was a correlation between the duration of standing position and complaints of MSDs (Pvalue=0.011; r=0.369; positive direction), no correlation between shoe type and complaints of MSDs (Pvalue=0.735; r=0.051; positive direction), and no correlation between the height of heels and complaints of MSDs (Pvalue=0.256; r=0.169; positive direction). It was concluded that there was a correlation between the duration of standing position and complaints of MSDs, and there was no correlation between shoe type and the height of heels with complaints of MSDs.